Highly-durable plasma-sprayed Al2O3-YSZ/YSZ double ceramic layer TBCs against CMAS corrosion - Zhang, Yongang; Gao, Wei; Dou, Mengfan; Han, Jiasen; Wu, Dongting; Zou, Yong (Journal of the European Ceramic Society, 2024)
The addition of Al2O3 inside thermal barrier coatings (TBCs) is highlighted effective on mitigating TBCs degradation induced by CMAS corrosion. In this study, the cost-effective 20 wt.%Al2O3-7YSZ/7YSZ double ceramic layer (DCL) TBCs were fabricated and their long-term performance resisting CMAS corrosion was investigated. Significant bending and CMAS infiltration occurred readily for the single layer 7YSZ coatings just after 5 h duration. The top sacrificial Al2O3-7YSZ layer of DCL coatings greatly constrained coating deflection and CMAS infiltration. This is due to the chemical reaction between alumina splats and CMAS, generating interconnected anorthites for effectively blocking CMAS infiltration and improving resistance to CMAS attack. However, it is highlighted that the role of alumina splats on mitigating CMAS degradation was found different between the short-term corrosion and long-term corrosion. In addition, interfacial delamination/cracking was not observed between the top Al2O3-7YSZ layer and bottom 7YSZ layer after 100 h CMAS corrosion, demonstrating superior interface integrity and durability.